Pengaruh Diameter Nossel Spraygun Terhadap Efesiensi Pengecatan - Kristanto, Yunus; Rubiono, Gatut; Mujianto, Haris (Virtual of Mechanical Engineering Article, 2017)
Painting is surface treatment that aimed to protect the surface and to increase the material value by layering a material with more valuable one. This knowledge is known as surface coating knowledge. This research is aimed to get the effect of nozzle spray gun hole diameter and spray distance due to painting efficiency. The research is done by laboratory experiment. Spray distance vary as 15 cm, 17 cm, 20 cm, 22 cm and 25 cm. Nozzle diameter vary as 1; 1,5 and 2 mm. The data are taken for area product of the painting and the thickness of the layer by measuring the weight of the material. The experiment use Avian Sea Blue paint and 17 x 20 cm zinc plate. The data taken for 3 times. The result shows that spray distance has effect due to painting area. Closer distance tend to decrease the diameter. If the spray distance is too close, it can cause the paint melt. Otherwise, the longer distance cause the paint dry before its stick to the media.